Navigating Digital Stress: A Rasch Analysis of Social Media Impact and Psychological Readiness among Female Teachers in Islamic Schools - Nisa, Auwliya Khairun; Aridan, Muhammad; Marzuki; Bhatti, Muhammad Safdar (WISE Pendidikan Indonesia, 2024)
This study investigates the psychological impact of social media on female teachers in Islamic schools and their readiness to manage its negative effects. Using a mixed-methods design and Rasch model analysis, data were collected from 621 teachers across diverse Indonesian regions. The findings reveal significant variations in perceived mental health impact and coping readiness based on age, education level, region, and social media usage patterns. Teachers with high engagement, especially on visual platforms like Instagram and TikTok, reported increased psychological stress. Rasch-based DIF analysis highlighted item-level disparities across demographic subgroups. The study offers a novel contribution by integrating Islamic concepts maqashid syariah, fitrah, and ihsan into the interpretation of digital mental health, emphasizing the spiritual and cultural dimensions of resilience. The results underscore the importance of culturally sensitive interventions that support both psychological well-being and religious identity. Limitations include the study’s cross-sectional nature and context-specific sample.